치열교정 환자의 전문가 칫솔질 및 구강보건교육에 따른 치면세균막 관리효과 - 김윤주; Yun Ju Kim; 정호진; Ho Jin Jeong; 윤정원; Jung Won Yun; 김예황; Yea Hwang Kim; 윤현서; Hyun Seo Yoon; 이선미; Sun Mi Lee; et al. (대한구강보건학회지, 2018)
Objectives: This study aimed to contribute to the development of an oral health education program on organized professional toothbrushing by determining its effects on plaque control in patients undergoing orthodontic treatment. Methods: The subjects in the experimental group participated in the professional toothbrushing and oral health education weekly for 4 weeks, and those in the control group participated in the same program without professional toothbrushing education. Results: The difference in knowledge, attitude, and behaviors on oral health was higher among the experimental group who underwent professional toothbrushing and oral health education program than those in the control group. The effects of toothbrushing time on the plaque index were significantly lower in experimental group than those in the control group. Conclusions: It is suggested that adequate oral health and professional toothbrushing education program should be implemented to improve oral health.